Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Placodiscus bijugus (Sapindaceae) a new species of Endangered lowland evergreen forest tree from the western foothills of Mt Cameroon and from Korup National Park, Cameroon - George Gosline; Nouhou Ndam; Stuart Cable; Martin Cheek (Kew Bulletin, 2025)
Summary A new range-restricted species of Placodiscus Radlk. is described, mapped and illustrated. Placodiscus bijugus is a cauliflorous tree (4 –) 5 – 10 m tall, characterised by having leaves with two pairs of leaflets, 1 (– 2)-flowered cymules with minute bracts, a glabrous disk, pedicels 3 – 3.2 mm long and large (3 – 4 cm diam.), shortly stipitate, retuse fruits, orbicular in outline. It is similar to P. caudatus Pierre ex Pellegr., which has been reported from surveys in Cameroon. We discuss the typification and range of the latter species, which in fact appears to be absent from Cameroon. Placodiscus bijugus is provisionally assessed as Endangered [EN B1ab(iii)+2ab(iii)] using the IUCN Red List Categories and Criteria, since only three locations with threats are reported. The species has a small, slightly disjunct range between Mt Cameroon and Korup National Park in coastal South West Region Cameroon. We review other species with this disjunct range.

Galactic cosmic ray environment predictions for the NASA BioSentinel Mission, part 2:Post-mission validation - Shirin Rahmanian; Tony C. Slaba; Stuart George; Leslie A. Braby; Sharmila Bhattacharya; Tore Straume; Sergio R. Santa Maria (Life Sciences in Space Research, 2025)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

The importance of time-resolved personal Dosimetry in space: The ISS Crew Active Dosimeter - Ramona Gaza; A. Steve Johnson; Bryan Hayes; Thomas Campbell-Ricketts; Jani Rakkola; Mena Abdelmelek; Cary Zeitlin; Stuart George; Nicholas Stoffle; Andrew Castro; Clif Amberboy; Edward Semones (Life Sciences in Space Research, 2023)

HERA: A Timepix-based radiation detection system for Exploration-class space missions - Nicholas N. Stoffle; Tom Campbell-Ricketts; Andrew Castro; Ramona Gaza; Cary Zeitlin; Stuart George; Mena Abdelmelek; Aaron Schram (Life Sciences in Space Research, 2023)

Particle showers detected on ISS in Timepix pixel detectors - Martin Kroupa; Thomas Campbell-Ricketts; Stuart P. George; Amir A. Bahadori; Lawrence S. Pinsky (Life Sciences in Space Research, 2023)

The impact of COVID-19 public health restrictions on particulate matter pollution measured by a validated low-cost sensor network in Oxford, UK - Tony Bush; Suzanne Bartington; Francis D. Pope; Ajit Singh; G. Neil Thomas; Brian Stacey; George Economides; Ruth Anderson; Stuart Cole; Pedro Abreu; Felix C.P. Leach (Building and Environment, 2023)

Structural response of a compliant pipe-in-pipe under frictionless and frictional conditions of the seabed - Auwalu I. Mohammed; Konstantinos Bartzas; Callum Johnson; Stuart Spence; Paul Skyes; George Kidd; Jennifer McConnachie; James Njuguna (Ocean Engineering, 2023)

Monitoring and modeling dispersal of a submerged nearshore berm at the mouth of the Columbia River, USA - Andrew W. Stevens; Hans R. Moritz; Edwin P.L. Elias; Guy R. Gelfenbaum; Peter R. Ruggiero; Stuart G. Pearson; James M. McMillan; George M. Kaminsky (Coastal Engineering, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Ecotrons: Powerful and versatile ecosystem analysers for ecology, agronomy and environmental science - Jacques Roy; François Rineau; Hans J. De Boeck; Ivan Nijs; Thomas Pütz; Samuel Abiven; John A. Arnone; Craig V. M. Barton; Natalie Beenaerts; Nicolas Brüggemann; Matteo Dainese; Timo Domisch; et al. (Global Change Biology, 2021)
Ecosystems integrity and services are threatened by anthropogenic global changes. Mitigating and adapting to these changes require knowledge of ecosystem functioning in the expected novel environments, informed in large part through experimentation and modelling. This paper describes 13 advanced controlled environment facilities for experimental ecosystem studies, herein termed ecotrons, open to the international community. Ecotrons enable simulation of a wide range of natural environmental conditions in replicated and independent experimental units while measuring various ecosystem processes. This capacity to realistically control ecosystem environments is used to emulate a variety of climatic scenarios and soil conditions, in natural sunlight or through broad‐spectrum lighting. The use of large ecosystem samples, intact or reconstructed, minimizes border effects and increases biological and physical complexity. Measurements of concentrations of greenhouse trace gases as well as their net exchange between the ecosystem and the atmosphere are performed in most ecotrons, often quasi continuously. The flow of matter is often tracked with the use of stable isotope tracers of carbon and other elements. Equipment is available for measurements of soil water status as well as root and canopy growth. The experiments ran so far emphasize the diversity of the hosted research. Half of them concern global changes, often with a manipulation of more than one driver. About a quarter deal with the impact of biodiversity loss on ecosystem functioning and one quarter with ecosystem or plant physiology. We discuss how the methodology for environmental simulation and process measurements, especially in soil, can be improved and stress the need to establish stronger links with modelling in future projects. These developments will enable further improvements in mechanistic understanding and predictive capacity of ecotron research which will play, in complementarity with field experimentation and monitoring, a crucial role in exploring the ecosystem consequences of environmental changes.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Redmap Australia: Challenges and Successes With a Large-Scale Citizen Science-Based Approach to Ecological Monitoring and Community Engagement on Climate Change - Gretta T. Pecl; Jemina Stuart-Smith; Peter Walsh; Dianne J. Bray; Martha Kusetic; Michael Burgess; Stewart D. Frusher; Daniel C. Gledhill; Oliver George; Gary Jackson; John Keane; Victoria Y. Martin; et al. (Frontiers in Marine Science, 2019)

Variation in DNA methylation is associated with migratory phenotypes of lake sturgeon Acipenser fulvescens in the St. Clair River, MI, USA - Justine M. Whitaker; Amy B. Welsh; Darryl W. Hondorp; James C. Boase; George T. Merovich; Stuart Welsh; Charles Krueger (Journal of Fish Biology, 2018)
Lake sturgeon Acipenser fulvescens populations show a variety of movement patterns that are poorly understood. To compare two migratory phenotypes of A. fulvescens in the St. Clair River, MI, USA, multiple data types were analysed. Individual fish were classified into migratory phenotypes based on acoustic telemetry data collected 2012–2015. Acipenser fulvescens consistently showed movement from the St. Clair River upriver into Lake Huron or downriver into Lake St. Clair. The two migratory phenotypes were then compared for differences in morphometrics, genetics and epigenetics. Morphological differences based on linear measurements were not detected between phenotypes. Microsatellite data from 11 loci suggested one population with no genetic differentiation between migratory phenotypes. Our epigenetic results indicated that the migratory phenotypes are differentially methylated ( P A. fulvescens . Only one restriction site was identified to be driving the differential methylation ( P A. fulvescens , DNA methylation may play a role in the observed movement pattern variation. When combined with microsatellite and morphometric analyses, our results suggested that different migratory patterns may reflect phenotypic plasticity, allowing A. fulvescens to acclimate to short‐term environmental variability. Without an integrated approach, the role of epigenetics in the migratory phenotype of A. fulvescens may have been overlooked. Further characterization of migratory phenotypes could be important for management to conserve behavioural variation across the distribution of A. fulvescens and for design of stocking guidelines.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Liposomal Amphotericin B as Monotherapy in Relapsed Coccidioidal Meningitis - Ethan R. Stewart; Matthew L. Eldridge; Ian McHardy; Stuart H. Cohen; George R. Thompson (Mycopathologia, 2018)

A cross‐continental comparison of assemblages of seed‐ and fruit‐feeding insects in tropical rain forests: Faunal composition and rates of attack - Yves Basset; Chris Dahl; Richard Ctvrtecka; Sofia Gripenberg; Owen T. Lewis; Simon T. Segar; Petr Klimes; Héctor Barrios; John W. Brown; Sarayudh Bunyavejchewin; Buntika A. Butcher; Anthony I. Cognato; et al. (Journal of Biogeography, 2018)
Aim Insects feeding on seeds and fruits represent interesting study systems, potentially able to lower the fitness of their host plants. In addition to true seed eaters, a suite of insects feed on the fleshy parts of fruits. We examined the likelihood of community convergence in whole insect assemblages attacking seeds/fruits in three tropical rain forests. Location Three Forest GEO permanent forest plots within different biogeographical regions: Barro Colorado Island (Panama), Khao Chong (Thailand) and Wanang (Papua New Guinea). Methods We surveyed 1,186 plant species and reared 1.1 ton of seeds/fruits that yielded 80,600 insects representing at least 1,678 species. We assigned seeds/fruits to predation syndromes on the basis of plant traits relevant to insects, seed/fruit appearance and mesocarp thickness. Results We observed large differences in insect faunal composition, species richness and guild structure between our three study sites. We hypothesize that the high species richness of insect feeding on seeds/fruits in Panama may result from a conjunction of low plant species richness and high availability of dry fruits. Insect assemblages were weakly influenced by seed predation syndromes, both at the local and regional scale, and the effect of host phylogeny varied also among sites. At the driest site (Panama), the probability of seeds of a plant species being attacked depended more on seed availability than on the measured seed traits of that plant species. However, when seeds were attacked, plant traits shaping insect assemblages were difficult to identify and not related to seed availability. Main conclusions We observed only weak evidence of community convergence at the intercontinental scale among these assemblages. Our study suggests that seed eaters may be most commonly associated with dry fruits at relatively dry tropical sites where fleshy fruits may be less prevalent.

Infections Up to 76 Days After Stroke Increase Disability and Death - Annastazia E. Learoyd; Lisa Woodhouse; Laurence Shaw; Nikola Sprigg; Daniel Bereczki; Eivind Berge; Valeria Caso; Hanne Christensen; Ronan Collins; Anna Czlonkowska; Anwar El Etribi; Tracy D. Farr; et al. (Translational Stroke Research, 2017)

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo - Nicolás M. Suárez; Betty Lau; George M. Kemble; Ronzo Lee; Edward S. Mocarski; Gavin W. G. Wilkinson; Stuart P. Adler; Michael A. McVoy; Andrew J. Davison (Virus Genes, 2017)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Ecological and socio-economic factors affecting extinction risk in parrots - George Olah; Stuart H. M. Butchart; Andy Symes; Iliana Medina Guzmán; Ross Cunningham; Donald J. Brightsmith; Robert Heinsohn (Biodiversity and Conservation, 2016)

Tiger (Panthera tigris) scent DNA: a valuable conservation tool for individual identification and population monitoring - Anthony Caragiulo; Rob Stuart Alexander Pickles; Joseph Alexander Smith; Olutolani Smith; John Goodrich; George Amato (Conservation Genetics Resources, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Upper mantle anisotropy of southeast Arabia passive margin [Gulf of Aden northern conjugate margin], Oman - Ali Al-Lazki; Cindy Ebinger; Michael Kendall; George Helffrich; Sylvie Leroy; Christel Tiberi; Graham Stuart; Khalfan Al-Toobi (Arabian Journal of Geosciences, 2012)

Crops that feed the world 4. Barley: a resilient crop? Strengths and weaknesses in the context of food security - Adrian Clive Newton; Andrew J. Flavell; Timothy S. George; Philip Leat; Barry Mullholland; Luke Ramsay; Cesar Revoredo-Giha; Joanne Russell; Brian J. Steffenson; J. Stuart Swanston; William T. B. Thomas; Robbie Waugh; et al. (Food Security, 2011)

Alternative (non-animal) methods for cosmetics testing: current status and future prospects—2010 - Sarah Adler; David Basketter; Stuart Creton; Olavi Pelkonen; Jan van Benthem; Valérie Zuang; Klaus Ejner Andersen; Alexandre Angers-Loustau; Aynur Aptula; Anna Bal-Price; Emilio Benfenati; Ulrike Bernauer; et al. (Archives of Toxicology, 2011)

A new dawn for industrial photosynthesis - Dan E. Robertson; Stuart A. Jacobson; Frederick Morgan; David Berry; George M. Church; Noubar B. Afeyan (Photosynthesis Research, 2011)

The pharmacokinetic profile of recombinant human erythropoietin is unchanged in patients undergoing cardiac surgery - Stuart A. McCluskey; Wing K. Cheung; Rita Katznelson; Humara Poonawala; Ludwik Fedorko; George Djaiani; Bobby Mehta; Keyvan Karkouti (European Journal of Clinical Pharmacology, 2009)

Experimental manipulations of microbial food web interactions in a humic lake: shifting biological drivers of bacterial community structure - Angela D. Kent; Stuart E. Jones; George H. Lauster; James M. Graham; Ryan J. Newton; Katherine D. McMahon (Environmental Microbiology, 2006)
Summary A previous multiyear study observed correlations between bacterioplankton community composition (BCC) and abundance and the dynamics of phytoplankton populations and bacterivorous grazers in a humic lake. These observations generated hypotheses about the importance of trophic interactions (both top‐down and bottom‐up) for structuring bacterial communities in this lake, which were tested using two multifactorial food web manipulation experiments that separately manipulated the intensity of grazing and the composition of the phytoplankton community. Our results, combined with field observations, suggest that a hierarchy of drivers structures bacterial communities in this lake. While other studies have noted links between aggregate measures of phytoplankton and bacterioplankton communities, we demonstrate here correlations between succession of phytoplankton assemblages and BCC as assessed by automated ribosomal intergenic spacer analysis (ARISA). We used a novel approach linking community ARISA data to phylogenetic assignments from sequence analysis of 16S rRNA gene clone libraries to examine the responses of specific bacterial phylotypes to the experimental manipulations. The synchronous dynamics of these populations suggests that primary producers may mediate BCC and diversity through labile organic matter production, which evolves in quality and quantity during phytoplankton succession. Superimposed on this resource‐mediated control of BCC are brief periods of intense bacterivory that impact bacterial abundance and composition.

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Quantitative trait loci for hip dysplasia in a crossbreed canine pedigree - Rory J. Todhunter; Raluca Mateescu; George Lust; Nancy I. Burton-Wurster; Nathan L. Dykes; Stuart P. Bliss; Alma J. Williams; Margaret Vernier-Singer; Elizabeth Corey; Carlos Harjes; Richard L. Quaas; Zhiwu Zhang; et al. (Mammalian Genome, 2005)

The extent and distribution of linkage disequilibrium in a multi-hierarchic outbred canine pedigree - Xiang-Yang Lou; Rory J. Todhunter; Min Lin; Qing Lu; Tian Liu; Zuoheng Wang; Stuart P. Bliss; George Casella; Gregory M. Acland; George Lust; Rongling Wu (Mammalian Genome, 2003)

Metronidazole resistance and microaerophily in Campylobacter species - M. A. Smith; Margaret A. Jorgensen; George L. Mendz; Stuart L. Hazell (Archives of Microbiology, 1998)

Twenty-Five Years of the Clean Water Act: How Clean Are Forest Practices? - George G. Ice; Gordon W. Stuart; Jack B. Waide; Lloyd C. Irland; Paul V. Ellefson (Journal of Forestry, 1997)

Pyruvate metabolism in Helicobacter pylori - George L. Mendz; Stuart L. Hazell; Leon van Gorkom (Archives of Microbiology, 1994)

Pyruvate metabolism in Helicobacter pylori - George L. Mendz; Stuart L. Hazell; Leon van Gorkom (Archives of Microbiology, 1994)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)